EXPLORING THE INFLUENCE OF CLASSROOM INTERACTION ON ACADEMIC COMMUNICATION SKILLS IN SECONDARY SCHOOLS: A CASE STUDY OF SELECTED SENIOR HIGH SCHOOLS IN THE TAHOUA REGION - TCHAGNONHOU, Dèkandé Sylvestre; ZOUNHIN TOBOULA, Coffi Martinien; HOUNYETIN, Claude (My University, 2023)
This study explored the relationship between classroom interaction and academic communication in secondary schools. The study was prompted by the low proficiency in English and French observed among students in the Faculty of Education in Tahoua after seven years of secondary education. The study adopted a mixed-methods research approach to uncover the reasons behind this situation, including classroom observations, semi-structured teacher interviews, a student questionnaire, and a controlled experiment. Data (quantitative and qualitative) were analysed through descriptive and inferential statistics and an inductive thematic approach. The study involved classroom observations in English and French language classrooms. In addition, the students (1391) were separated into two groups for the experiment: an experimental group that utilised interactive teaching methods and a control group that followed traditional methods. The results of the three-month experiment revealed that the experimental group exhibited enhanced oral communication skills compared to the control group, suggesting that classroom interaction is a key factor in academic communication. The findings of this study underline the importance of incorporating interactive teaching strategies in the classroom to enhance student communication skills.
Keywords: Classroom interaction; Academic communication; Secondary schools; Mixed-methods research; Interactive teaching strategies